STATUS OF DELIVERED DOSE OF HEMODIALYSIS IN SAMPLE OF IRAQI PATIENTS - Ola Mohammed; Dr. Jawad Ibrahim; Rasheed Al Sheriff (Western European Studies, 2024)
Chronic kidney disease (CKD) has been and continues to be one of the leading causes of death and morbidity worldwide. Dialysis is considered one of the most important methods in the treatment of chronic kidney disease, and the issue of the ideal dose and frequency of dialysis has been at the forefront of important topics in dialysis treatment. Therefore, it may be possible to reduce morbidity and mortality by regularly assessing the dialysis dose provided to patients
Keywords: to evaluate the delivered; dose of dialysis